Thailand's Middle-Income Trap: Brain Drain and Seniority Culture - A Study of Skilled Labor Migration - Manowong, Anthika (Syntax Literate, 2025)
Thailand's manufacturing-focused industrial development has stagnated in the middle-income trap since the 1980s, largely due to its struggle to retain skilled engineers amid an aging population crisis. Research including focus group surveys of Thai engineers reveals that unfair employment practices and rigid seniority systems drive talent abroad, creating a brain drain. While late-developing countries can typically benefit from existing technologies and economies of scale, Thailand's progress is hindered by an education system that underemphasizes STEM fields. Additionally, although trade liberalization should theoretically aid development, it has instead reinforced global inequalities, making it harder for Thailand to achieve high-income status while experiencing continuous talent exodus. Keywords: Thailand, Middle-Income Trap, Skilled Labour, Brain Drained, Neoliberalism